(untitled) (Ciudades, 2018)
An urban model, intended to be sustainable, should start to recognize and valorize the structural role that the landscape and the nature play in the present urban configuration, and in the future development of an inhabitable environment as well. This text makes reference to the actuation proposals for four towns in Castilla y Leon through the instrument of planning, analyzing in each case its suitability and validity in its territorial variation. The importance of valuing the inherited pre-existences, the protection of the landscape, and a special attention paid to those singular areas and their identities, are common objectives for the interventions in Zamora, Valladolid, Villamuriel de Cerrato (Palencia) and Segovia; these objectives must be achieved through structural actions that should articulate the quality development of these towns and their territory.